A Comprehensive Compensation Method for High-speed Gear Pumps Without the Cavitation Phenomenon - Li Yulong; Hou Xinyu; Zhang Lihua (Jixie chuandong)
In order to improve the cavitation performance under high-speed for external gear pumps, a comprehensive compensation method with the small backlash, innovative annulus relief-groove and increasing inlet oil-pressure is proposed. Based on all derived models of the trapped-oil expansion-process interval, trapped-oil volume change rate, compensation flow rate for the expanded trapped-oil, relief areas and trapped-oil pressures differently under large backlash or small backlash, the minimum trapped-oil pressures under conventional rectangular relief-groove and innovative annular relief-groove are compared with an example. All results show that the maximum trapped-oil expansion rate and the expansion interval under the large backlash are only 18.3% of those of the small backlash; the maximum relief-area of the trapped-oil in the large backlash is only 7.9% of that in the small backlash due to different relief-groove space; the cavitation phenomenon is more serious; the ripple range of the trapped-oil pressure in the large backlash is 1.93 times than that in the small backlash, etc. It is concluded that the cavitation phenomenon of the high speed gear pump can be effectively alleviated by the comprehensive compensation method with the small backlash, innovative annular relief-groove and increasing inlet oil-pressure.